Varus knee osteoarthritis: Elevated synovial CD15 counts correlate with inferior biomechanical properties of lateral‐compartment cartilage. Issue 3 (29th August 2017) - Koller, Ulrich; Waldstein, Wenzel; Krenn, Veit; Windhager, Reinhard; Boettner, Friedrich
ABSTRACT: The study analyzed the influence of synovitis on the histological and biomechanical properties of lateral‐compartment cartilage. In a prospective cohort study, 84 patients (100 knees) with varus deformity of the knee were included. Osteochondral samples from the distal lateral femur underwent biomechanical and histologic analysis. Synovial tissue was sampled for histological (chronic synovitis score) and immunohistochemical evaluation of the degree of synovitis. CD15 (neutrophils), Ki‐67 (dividing cells), and CD68 (macrophages) were tested in all synovial samples. While the histological synovitis score did not correlate with the degree of cartilage degeneration (histological OARSI grades), both CD15 ( r s = 0.297, p = 0.006) and Ki‐67 ( r s = 0.249, p = 0.023) correlated with histological OARSI grades. There was a weak negative correlation of CD15 with biomechanical properties of cartilage of the distal lateral femur (aggregate modulus (Ha): r s = −0.125; p = 0.257; dynamic modulus (DM): r s = −0.216; p = 0.048). No correlations were observed for Ki‐67 and CD68. In addition, biomechanical properties were inferior in knees with a CD15 of >8/high power field compared to knees with a CD15 of ≤8/high power field (Ha: p = 0.031, d = 0.46; DM: p = 0.005, d = 0.68). The study demonstrates an association of increased inflammatory activity with advanced cartilage degeneration. Lateral‐compartment cartilage in knees with elevated synovial CD15 counts has a reduced ability to withstand compressive loads. CD15 might serve as an indicator for inferior biomechanical cartilage properties. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:841–846, 2018.